Get insightful responses to your questions quickly and easily on IDNLearn.com. Get comprehensive answers to all your questions from our network of experienced experts.
Sagot :
To solve the equation [tex]\(\frac{5}{x+2} + \frac{3}{x-3} = 2\)[/tex], we will go through the following steps:
1. Combine the fractions on the left-hand side.
2. Clear the denominators by multiplying through by the common denominator.
3. Simplify the resulting equation.
4. Solve for [tex]\(x\)[/tex].
5. Check the solutions in the original equation to ensure they are valid.
Let's begin:
### Step 1: Combine the fractions
We need a common denominator to combine the fractions on the left-hand side. The common denominator of [tex]\(x+2\)[/tex] and [tex]\(x-3\)[/tex] is [tex]\((x+2)(x-3)\)[/tex]. Rewriting the fractions with this common denominator, we have:
[tex]\[ \frac{5(x-3)}{(x+2)(x-3)} + \frac{3(x+2)}{(x+2)(x-3)}. \][/tex]
Combining these fractions, we get:
[tex]\[ \frac{5(x-3) + 3(x+2)}{(x+2)(x-3)} = 2. \][/tex]
### Step 2: Clear the denominators
Multiply both sides of the equation by the common denominator [tex]\((x+2)(x-3)\)[/tex] to clear the fractions:
[tex]\[ 5(x-3) + 3(x+2) = 2(x+2)(x-3). \][/tex]
### Step 3: Simplify
Expand both sides of the equation:
[tex]\[ 5x - 15 + 3x + 6 = 2(x^2 - x - 6). \][/tex]
Combine like terms on the left-hand side:
[tex]\[ 8x - 9 = 2x^2 - 2x - 12. \][/tex]
Move all terms to one side to set the equation to zero:
[tex]\[ 2x^2 - 2x - 12 - 8x + 9 = 0. \][/tex]
Simplify further:
[tex]\[ 2x^2 - 10x - 3 = 0. \][/tex]
### Step 4: Solve for [tex]\(x\)[/tex]
We have a quadratic equation [tex]\(2x^2 - 10x - 3 = 0\)[/tex].
Now, we can use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 2\)[/tex], [tex]\(b = -10\)[/tex], and [tex]\(c = -3\)[/tex]:
[tex]\[ x = \frac{-(-10) \pm \sqrt{(-10)^2 - 4(2)(-3)}}{2(2)}. \][/tex]
Simplifying inside the square root:
[tex]\[ x = \frac{10 \pm \sqrt{100 + 24}}{4}, \][/tex]
[tex]\[ x = \frac{10 \pm \sqrt{124}}{4}, \][/tex]
[tex]\[ x = \frac{10 \pm 2\sqrt{31}}{4}, \][/tex]
[tex]\[ x = \frac{5 \pm \sqrt{31}}{2}. \][/tex]
So, the solutions to the equation are:
[tex]\[ x = \frac{5 - \sqrt{31}}{2} \quad \text{and} \quad x = \frac{5 + \sqrt{31}}{2}. \][/tex]
### Step 5: Check the solutions
Finally, we should check these solutions in the original equation to verify their validity. Upon substitution, both these values satisfy the original equation [tex]\(\frac{5}{x+2} + \frac{3}{x-3} = 2\)[/tex].
Therefore, the solutions to the equation [tex]\(\frac{5}{x+2} + \frac{3}{x-3} = 2\)[/tex] are:
[tex]\[ \boxed{\frac{5 - \sqrt{31}}{2}} \quad \text{and} \quad \boxed{\frac{5 + \sqrt{31}}{2}}. \][/tex]
1. Combine the fractions on the left-hand side.
2. Clear the denominators by multiplying through by the common denominator.
3. Simplify the resulting equation.
4. Solve for [tex]\(x\)[/tex].
5. Check the solutions in the original equation to ensure they are valid.
Let's begin:
### Step 1: Combine the fractions
We need a common denominator to combine the fractions on the left-hand side. The common denominator of [tex]\(x+2\)[/tex] and [tex]\(x-3\)[/tex] is [tex]\((x+2)(x-3)\)[/tex]. Rewriting the fractions with this common denominator, we have:
[tex]\[ \frac{5(x-3)}{(x+2)(x-3)} + \frac{3(x+2)}{(x+2)(x-3)}. \][/tex]
Combining these fractions, we get:
[tex]\[ \frac{5(x-3) + 3(x+2)}{(x+2)(x-3)} = 2. \][/tex]
### Step 2: Clear the denominators
Multiply both sides of the equation by the common denominator [tex]\((x+2)(x-3)\)[/tex] to clear the fractions:
[tex]\[ 5(x-3) + 3(x+2) = 2(x+2)(x-3). \][/tex]
### Step 3: Simplify
Expand both sides of the equation:
[tex]\[ 5x - 15 + 3x + 6 = 2(x^2 - x - 6). \][/tex]
Combine like terms on the left-hand side:
[tex]\[ 8x - 9 = 2x^2 - 2x - 12. \][/tex]
Move all terms to one side to set the equation to zero:
[tex]\[ 2x^2 - 2x - 12 - 8x + 9 = 0. \][/tex]
Simplify further:
[tex]\[ 2x^2 - 10x - 3 = 0. \][/tex]
### Step 4: Solve for [tex]\(x\)[/tex]
We have a quadratic equation [tex]\(2x^2 - 10x - 3 = 0\)[/tex].
Now, we can use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 2\)[/tex], [tex]\(b = -10\)[/tex], and [tex]\(c = -3\)[/tex]:
[tex]\[ x = \frac{-(-10) \pm \sqrt{(-10)^2 - 4(2)(-3)}}{2(2)}. \][/tex]
Simplifying inside the square root:
[tex]\[ x = \frac{10 \pm \sqrt{100 + 24}}{4}, \][/tex]
[tex]\[ x = \frac{10 \pm \sqrt{124}}{4}, \][/tex]
[tex]\[ x = \frac{10 \pm 2\sqrt{31}}{4}, \][/tex]
[tex]\[ x = \frac{5 \pm \sqrt{31}}{2}. \][/tex]
So, the solutions to the equation are:
[tex]\[ x = \frac{5 - \sqrt{31}}{2} \quad \text{and} \quad x = \frac{5 + \sqrt{31}}{2}. \][/tex]
### Step 5: Check the solutions
Finally, we should check these solutions in the original equation to verify their validity. Upon substitution, both these values satisfy the original equation [tex]\(\frac{5}{x+2} + \frac{3}{x-3} = 2\)[/tex].
Therefore, the solutions to the equation [tex]\(\frac{5}{x+2} + \frac{3}{x-3} = 2\)[/tex] are:
[tex]\[ \boxed{\frac{5 - \sqrt{31}}{2}} \quad \text{and} \quad \boxed{\frac{5 + \sqrt{31}}{2}}. \][/tex]
Your participation means a lot to us. Keep sharing information and solutions. This community grows thanks to the amazing contributions from members like you. IDNLearn.com has the solutions to your questions. Thanks for stopping by, and come back for more insightful information.